Delta Raiders: A study of collective narratives within veterans’ reunions. - Blackman, Aaron C. (Kansas State University, 2011)
This study examines the therapeutic nature of veterans’ reunions through a qualitative analysis of interviews and participant observation of the 2010 Delta Raiders of Vietnam Association biannual reunion. Eight Vietnam veterans who served in the 2nd Battalion, 501st Infantry, 101st Airborne Division (Airmobile), Company D during Vietnam were interviewed, as well as three wives of these veterans. The following research question directed the study: What communicative functions do veterans’ reunions serve? By examining the quality of social support and the rationality (probability and fidelity) of the narratives that these veterans provide one another, this study seeks to understand why Vietnam veterans continue meeting for reunions, what in particular is so strong about the Delta Raider reunions, and how personal narratives communicatively function within a veteran’s reunion context. Results show that the veterans’ reunions primarily serve to rebuild narrative probability for the veterans, as well as construct boundaries for narrative fidelity to work within. Additionally, veterans’ reunions provide therapeutic relief, forming a second family through renewed company pride, and revealing tension between shared veteran experience and family communication.
Keywords: Veteran; Narrative; Reunion; Communication (0459)